(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The Constitutionalist Sensibility of Italian Canonists prior to Vatican II ABSTRACT: The paper traces the main contributions of Italian canonists to canonical constitutionalism prior to Vatican II. Starting with Emmanuele de Sarzana’s textbook, it examines Giuseppe Forchielli’s proposal in the debate on the Ecclesiastical Law Archive and the approach of Bertola, Ragazzini and Ferrante’s texts. Special attention is paid to the foundations and contributions of the so-called Italian dogmatic school (Del Giudice, Giacchi, d’Avack and others). Systematic approach and dialogue with secular culture dispose to the acquisition of constitutionalist categories; however, mature and thoughtful elaborations of the modern constitutional approach are not yet found. Prior to the Second Vatican Council, the ecclesiological and conceptual premises (fundamental equality and charismatic variety) for a change of approach to canonical juridicity are lacking. The hierarchical structural and organizational aspect tends to prevail over the centrality of the person and the community. The juridical-dogmatic imprint, purified of positivistic and structuralist deviations, can form the basis for the maturation of a constitutional paradigm. SOMMARIO - 1. Il senso di una ricerca storica parziale e settoriale - 2. Un antesignano del sistema costituzionale? - 3. La proposta del Forchielli e il dibattito coevo - 4. L’esplicita emersione dell’esigenza costituzionale - 4.1. Il corso di Bertola - 4.2. L’indagine sulla potestà di Ragazzini - 4.3. La ‘Summa juris constitutionalis Ecclesiae’ del Ferrante - 5. Il contesto stimolante della dottrina laica italiana e la teoria sull’ordinamento canonico - 6. I limiti dell’impostazione costituzionalistica anteriore al Vaticano II - 7. Il legato di un approccio culturale originale.